2020
DOI: 10.1016/j.jenvp.2020.101473
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and demographic predictors of plastic bag consumption in transaction data

Abstract: Despite the success of plastic bag charges in the UK, there are still around a billion single-use plastic bags bought each year in England alone, and the government have made plans to increase the levy from 5 to 10 pence. Previous research has identified motivations for bringing personal bags to a supermarket, but little is known about the individuals who are continuing to frequently purchase single-use plastic bags after the levy. In this study, over a million loyalty card transaction records from a high-stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 76 publications
0
13
0
1
Order By: Relevance
“…Six months after implementing the charge for plastic bags in England, it was verified that the number of disposable plastic bags used dropped by more than 85%, around 500 million units. Likewise, there was an increase in the awareness of the environmental impact of household plastic waste and the population's support for the issue [24]. Studies carried out reveal that the reduction policy is effective, instigating the consumer to avoid the use of plastic bags across 52.3% a year [39].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Six months after implementing the charge for plastic bags in England, it was verified that the number of disposable plastic bags used dropped by more than 85%, around 500 million units. Likewise, there was an increase in the awareness of the environmental impact of household plastic waste and the population's support for the issue [24]. Studies carried out reveal that the reduction policy is effective, instigating the consumer to avoid the use of plastic bags across 52.3% a year [39].…”
Section: Discussionmentioning
confidence: 99%
“…Consumers are increasingly concerned about the safety offered by the products which they consume, such as food, water, health-related products such as medicines and other goods used in everyday life [20]. Lavelle-Hill et al [24] verified that people more concerned with environmental issues are currently younger, female, have more money and a higher education. They found that young adults are more concerned with the environment, but older adults adopt more pro-environmental behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations